FORMAT – Building an Original Methodology for Technology Forecasting through Researchers Exchanges between Industry and Academia. (2015) - Cascini, Gaetano; Becattini, Niccolò; Kaikov, Igor; Koziolek, Sebastian; Kucharavy, Dmitry; Nikulin, Christopher; Petrali, Pierluigi; Slupinsky, Mateusz; Rabie, Mahmoud; Balachandar,; Ramadurai,; Ruggeri, Luca; et al.
Abstract: The paper presents an overview of the FORMAT methodology, an approach for technological forecasting capable of satisfying the need of manufacturing industries to better support decision-making processes in planning corporate strategies for R&D. The methodology has been developed within the FORMAT consortium, gathering partners from both industry and academia in a Marie-Curie EU funded project of the 7th Framework Programme - IAPP PEOPLE. The methodology is intentionally shaped as a generic one, so as to foster its adoption by the wider audience, but it suggests the adoption of several TRIZ techniques and models to support the forecast. Its exemplary application in the field of forming technologies for domestic refrigerators aims at showing its potential and viability in a real industrial context. The paper is supplemented by a case study in the white goods manufacturing (forming techniques for the inner liners of domestic refrigerators).